SYMMETRIC AND ASYMMETRIC EFFECTS OF MONETARY POLICY SHOCKS ON OUTPUT IN BRICS COUNTRIES: EVIDENCE FROM HIDDEN PANEL COINTEGRATION - Bayat, Tayfur; Tutgun, Seyhun; Tasar, Izzet (Editura Ase, 2021)
Monetary policy and its possible effects on total output has been discussed both theoretically and empirically by many economic schools within the framework of economic theory. This study questions the symmetric and asymmetric effects of monetary policy shocks on output in the BRICS countries for the period of 1997-2019 were analyzed using hidden panel data method. According to the empirical analysis results, monetary policy does not have a symmetrical effect on output. Asymmetric effects on the other hand valid from negative and positive shocks of monetary policy to positive and negative shocks of output respectively in the short and also in the long run.
Keywords: Monetary Policy; Symmetric Effect; Asymmetric Effect; BRICS